Sensitive Spectrophotometric Determination of Tetracycline Hydrochloride Indosage forms using Sodium Nitroprusside and Hydroxylamine Hydrochloride - Hadi, Hind; Fadhil, Ghadah (Al-Nahrain Journal of Science, 2018)
An optimized and validated spectrophotometric method has been developed for the determination of Tetracycline hydrochloride (TCH) in pharmaceutical formulations. The method is based on the reaction between TCH, sodium nitroprusside and hydroxylamine hydrochloride in alkaline medium. The product absorbed maximally at 529 nm. Beer’s law is obeyed in the working concentration range of 2-60 µg mL-1 with apparent molar absorptivity of 5.049×103 L mol-1cm-1 and Sandell’s sensitivity of 0.0952 µg cm2/ 0.001 absorbance unit. The proposed procedure was applied successfully for estimation of drug in different commercial forms. The proposed method was applied to the determination of the studied drug in pharmaceutical formulations and the results demonstrated that the method is equally accurate and precise as the official method as found from the t- and F-values.